Oxford American Handbook of Psychiatry, 1st Edition - Kupfer, David J., Horner, Michelle S.; Brent, David A.; Lewis, David A.; Reynolds, Charles F.; Thase, Michael E.; Trav (OXFORD UNIVERSITY PRESS, 2008)
Now is the most exciting time to be working in the field of psychiatry. Since the beginning of recorded history, mental or psychiatric illnesses (or disease) have been regarded with fear, disbelief, and superstition. These attributions have often been accompanied by fantastic descriptions of both the causes and treatments of these illnesses. Unfortunately, there exists a false separation of psychiatric illnesses from â€œphysical illnesses,â€ despite conclusive proof that all of the core psychiatric diseases are associated with changes in brain function or structure or both. This separateness means that psychiatry remains dogged by stigma, even from our colleagues in other medical specialties. Psychiatric diseases are more common than almost any other type of disease and among the most serious chronic conditions from which a person can suffer in terms of morbidity and shortened life expectancy. The important World Health Organization (WHO) and World Bank studies and analyses continue to substantiate this point of view. To truly understand psychiatry, one has to consider the centrality of the brain and its functioning to the organism as whole. Furthermore, the brain is an organ that develops and changes throughout life. Everything that an individual experiences in their life, every emotion, every memory, every interaction is processed by this changing organ. The human body comprises a system of pumps, filters, glands, conduits and mechanical systems whose primary aim is to support the brain, the organ that controls the system as a whole and the complexity of whose function makes us human. To separate mind from body is akin to trying to divorce the function of the heart from that of the lungs, since disease in one can lead to malfunction and disease in the other. The brain is as intimately connected with all the organs of the body as the right ventricle is to the pulmonary arteries. It, therefore, follows, and is clear from the literature, that there are psychiatric sequelae from physical illness just as there are physical sequalae from psychiatric illness. One of the perceived problems with psychiatry has been that the majority of diagnoses and treatments are based on the subjective description of symptoms by the sufferer and, therefore, somehow, the diseases are less valid than those where a rapidly available test can indicate the presence or absence of disease